Hungary’s correspondence with the EU regulations regarding liquid bio fuels - Kormányos, Szilvia (Acta Agraria Debreceniensis, 2008)
During the recent years researchers from different countries have found that our environment is at risk. It has been recognised by the leaders of the member countries and they have made decisions together concerning environmental protection in several agreements, contracts. Unfortunately, these decisions have been weakened and adumbrated on numerous occasions by certain interests. However, the energetic exploitation of the biomass has been supported by the economic and social changes of the previous years, more specifically, that of the bio fuels. The significant increase in the price of the traditional energy sources, the import dependency of the countries, the foreseeable exhaustion of the resources, the changes occurred due to joining the EU are all such problems that facilitates the application of bio fuels, as a good solution. Our country decided to modify the then existed bio fuel component rate of 2% to 5.75% which has to be achieved by 2010. Since then, in March 2007 it has been expanded to 10% until 2020 (concerning energy content). This decision was taken knowing that this year (2006) the bio fuel rate has been 0.5%. However, the rate of 2% has not been achieved even in the EU. One can understand that the implementation cannot be fulfilled without significant political decisions and support. The main reason for this is that the price of bio fuels is not competitive with the present fossil-origin energy prices in Hungary. So in 2007 several regulations were modified. The most important one is perhaps the regulation of the revenue tax, which caused the successful tax-differentiation concerning bio fuels in more member states between 2007 and 2008. Its essence is that the revenue tax is not decreased, but if the fuel does not contain a bio fuel component of 4.4 bulking percentage per litre, „punishment” tax has to be paid. Moreover, on behalf of the implementation, regulations concerning bio fuels and bio fuel components are improving At present the production and the application of bio fuels without any support are not economical yet. That is why it is important to emphasize the support policy of our country. After joining the Union, the new members can receive some shares from the direct disbursements, but only a tan increasing rate, we can achieve the 100% in 2013, though there is an opportunity for national contribution. Energy plants produced in agriculture receive separate supplementary support which is an advantageous opportunity for the farmers of the sector. Bio fuels cannot only be supported through agriculture, of course, but by research development, investment etc. All in all, it can be concluded that Hungary seeks to fulfil the EU responsibilities taken and by this, to contribute to the maintenance of the sustainable progress, decrease of environmental pollution and the import dependency of energy sources.